Impact of multi-site clinical trial results on clinical practice: Use of risperidone to treat PTSD nationally in the veterans health administration. (March 2023) - Rosenheck, Robert; Kurtz, Stephen G.; Anand, Sonia T.; Hau, Cynthia; Smedberg, Diane; Sicilia, Rosmery; Pontzer, James F.; Ferguson, Ryan E.
Highlights: This study examined the effect of a multi-site veterans health administration VHA trail of risperidone for PTSD on practice nationally in VHA. The trial had null results but use of this treatment for PTSD had already declined before publication. The trial did not affect VHA practice. Null results may be especially likelh to have limited impact on practice. Abstract: Multi-site randomized effectiveness trials evaluate treatments under real-world conditions. Whether results change practice is under-studied. A 6-month 26-site Veterans Health Administration (VHA) cooperative study published in 2011 compared an oral second-generation antipsychotic, risperidone, to placebo for refractory PTSD with null results. National VHA administrative data compared new starts on risperidone during the 5 years before and after the year of publication. Among the 450, 000–841, 000 Veterans diagnosed with PTSD annually from 2006 to 2016 the proportion with new starts on risperidone declined every year before and after publication. No evidence of an effect of null study results on VHA clinical practice was observed.